Panorama of fetal malformations at the maternity of Treichville teaching hospital (Abidjan - Côte d’Ivoire) - Yao, Ignace N’guessan; Dia, Jean-Marc Lamine; Adunfé Oyeladé, Mouhideen; Kouamé Bohoussou, Paul-Eric; N’guessan, Edouard Konan; Okon, Gérard; Guié, Privat Yéret; Anongba, Simplice Danho (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Congenital malformation is responsible for spontaneous abortion, the birth of a child born dead or a child with disabilities that can lead to long-term disability and have a detrimental impact on the individual, his family and society. The etiologies are diverse. The discovery in our maternity is not rare. The absence and high cost of these prenatal diagnostic are a brake on the detection of congenital malformations. It is these various malformations diagnosed in the ante natal and at birth in our service that we describe in this work which aims to make their panorama. Methods: The purpose of this cross-sectional and descriptive study curried out between 1 January 2003 and 31 December 2013 (10 years) was to describe the various congenital malformations observed at the maternity of the Gynecology and Obstetrics ward of the Treichville University Hospital Center and to identify the socio-demographic characteristics of mothers. This study concerned all women who had given birth at the Treichville University Hospital Center and whose child had a malformation. Results: During the period, 151 parturients gave birth to at least one child with a congenital malformation and among 30,698 newborns, 161 newborns (0.52%) had a malformation. Pregnant women were between 20 and 30 years old (66%), were primiparous in 46.4% of the cases, and 41.7% were housewives. The malformations were isolated in 101 newborns (62.4%), multiple in 60 newborns (37.6%), and dominated by those of the osteoarticular system and the nervous system. Fetal malformations had a poor prognosis in 77 cases (48%) and the fetus was stillborn in 44 cases (27%). Conclusions: Congenital malformations are a reality at the maternity clinic at Treichville. In our countries, the ultrasound stays a fundamental element for the congenital diagnosis of the malformations. A good training of the doctors in prenatal diagnosis is also necessary to make of good diagnoses who will allow a better care of new-born.